Satisfied, but Will They Spread a Word? The Role of Customer Satisfaction at Jamu CafÃ© - Suhud, Usep; Bajunaid, Sheila Maryam (Bina Nusantara University, 2018)
This research aimed to investigate consumersâ intention to repurchase jamu at Jamu CafÃ©. Service quality, customer satisfaction, and Word-of-Mouth (WOM) were selected as the predictor variables. In total, 200 participants who purchased jamu at the cafÃ© were selected conveniently. Data were analyzed using exploratory and confirmatory factor analyses as well as Structural Equation Model (SEM). As a result, service quality influences customer satisfaction significantly. As customers are satisfied, they do word-of-mouth and repurchase. On the other hand, WOM has an insignificant impact on repurchase intention.